2021
DOI: 10.1039/d1ta00103e
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of bulky imidazolium cation storage in dual graphite batteries: a spectroscopic and theoretical investigation

Abstract: Dual graphite batteries (DGBs) employ graphite as an intercalation host and store energy using the redox reactions of ionic liquid electrolyte–derived ions with graphite electrodes. As bulky (e.g., imidazolium-based) cation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…According to the first‐principles calculations, the total energy of intercalation models is −962.2 eV, which is less than the total energy of the adsorption model (−961.0 eV). This proves that the anions intercalation reaction typically occurs instead of the adsorption process, which is reasonably consistent with the principles of physics [58] . It is crucial to improve the reversible intercalation/deintercalation of anions to achieve a higher energy density for DGBs+K.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…According to the first‐principles calculations, the total energy of intercalation models is −962.2 eV, which is less than the total energy of the adsorption model (−961.0 eV). This proves that the anions intercalation reaction typically occurs instead of the adsorption process, which is reasonably consistent with the principles of physics [58] . It is crucial to improve the reversible intercalation/deintercalation of anions to achieve a higher energy density for DGBs+K.…”
Section: Resultssupporting
confidence: 82%
“…This proves that the anions intercalation reaction typically occurs instead of the adsorption process, which is reasonably consistent with the principles of physics. [58] It is crucial to improve the reversible intercalation/deintercalation of anions to achieve a higher energy density for DGBs + K.…”
Section: Chemelectrochemmentioning
confidence: 99%
“…Hence, those data suggested that graphite surface defects could be introduced not only during sonication (minor) but also during the charge/discharge cycling of DIBs (major). [ 24 ] The presence of defects is known to hinder the intercalation of AlCl4 between graphene layers and thus decrease the specific capacity of the graphite electrode. (DMPI + )(AlCl4 ) IL electrolyte was mainly kept in the glass fiber separator of spent DIBs (Figure 2g).…”
Section: Resultsmentioning
confidence: 99%
“…Cations and anions of the ILs can also be intercalated into the host materials, though limited study has been observed on this concept both experimentally and computationally [25,27,70–72] . In general, carbonaceous host materials such as graphite and polycyclic aromatic hydrocarbons (PAHs) are used as electrodes, which have enough space to accommodate the large size cations and anions of ILs [50] .…”
Section: Electrode Design For Dibsmentioning
confidence: 99%
“…Cations and anions of the ILs can also be intercalated into the host materials, though limited study has been observed on this concept both experimentally and computationally. [25,27,[70][71][72] In general, carbonaceous host materials such as graphite and polycyclic aromatic hydrocarbons (PAHs) are used as electrodes, which have enough space to accommodate the large size cations and anions of ILs. [50] We have conceptually demonstrated the dual graphite battery (DGB) with DMPI-AlCl 4 ionic liquid electrolyte, upon mixing of 1 : 1 ratio of 1,2-dimethyl-3propyl imidazolium chloride (DMPIÀ Cl) and AlCl 3 salt.…”
Section: Ionic Liquid Intercalating Electrodesmentioning
confidence: 99%